Diet modification challenges faced by marginalized and nonmarginalized adults with type 2 diabetes: A systematic review and qualitative meta-synthesis. (September 2017) - Vanstone, Meredith; Rewegan, Alex; Brundisini, Francesca; Giacomini, Mita; Kandasamy, Sujane; DeJean, Deirdre
Objectives: Diet modification is an important part of the prevention and treatment of type 2 diabetes, but sustained dietary change remains elusive for many individuals. This paper describes and interprets the barriers to diet modification from the perspective of people with type 2 diabetes, paying particular attention to the experiences of people who experience social marginalization. Methods: A systematic review of primary, empirical qualitative research was performed, capturing 120 relevant studies published between 2002 and 2015. Qualitative meta-synthesis was used to provide an integrative analysis of this knowledge. Results: Due to the central role of food in social life, dietary change affects all aspects of a person's life, and barriers related to self-discipline, emotions, family and social support, social significance of food, and knowledge were identified. These barriers are inter-linked and overlapping. Social marginalization magnifies barriers; people who face social marginalization are trying to make the same changes as other people with diabetes with fewer socio-material resources in the face of greater challenges. Discussion: A social-ecological model of behavior supports our findings of challenges at all levels, and highlights the need for interventions and counseling strategies that address the social and environmental factors that shape and sustain dietary change.